Double volume exchange transfusion in neonates with severe jaundice in the era of light emitting diode phototherapy - Pradhan, Monalisa; Anjali Sharma; Aswathaman, Nalini; Sriram, P. (International Journal of Contemporary Pediatrics, 2026)
Neonatal jaundice, though a common clinical condition, severe hyperbilirubinemia necessitating exchange transfusion remains a concern due to acute bilirubin encephalopathy and long-term neurodevelopmental sequelae. Exchange transfusion has drastically reduced after Light emitting diode-intensive phototherapy. This study analyzed the clinico-etiological profile of jaundiced neonates who underwent double-volume exchange transfusion in a tertiary care center. This hospital-based descriptive cross-sectional study was conducted on neonates who underwent exchange transfusion from May to October 2024 over six months. Data obtained by structured proforma was analyzed with descriptive statistics. Among 9 neonates who had double volume exchange transfusion, 7 were boys and 5 were outborn. Their mean gestational age was 37.1 weeks and birth weight ranged from 1350 to 3720 gm. The etiologies identified include Rh incompatibility (1 case), prematurity (1 case), unknown (4 case) and 3 cases with multiple etiology (one with G6PD deficiency, OB incompatibility and Gilbert syndrome, one baby with G6PD deficiency and OB incompatibility, another baby with late onset neonatal sepsis with G6PD deficiency). Their peak serum bilirubin levels ranged from 19 to 45 mg/dl. Two neonates required multiple exchange transfusions. Post-exchange transfusion, 5 neonates had thrombocytopenia. Maximum modified bilirubin-induced neurological dysfunction score was 10/12 in one neonate with G6PD deficiency and OB incompatibility. This study reemphasizes severe neonatal jaundice requiring exchange transfusion still exists. We recommend community-level implementation of mandatory routine screening, early identification, and timely referral for neonatal jaundice by ASHA workers.